Bi-directional relationships of arterial stiffness with hypertension and diabetes mellitus from the early pathophysiological stages: a 16-year prospective observational study. (3rd October 2022) - Nakano, H; Shiina, K; Takahashi, T; Fujii, M; Iwasaki, Y; Matsumoto, C; Yamashina, A; Chikamori, T; Tomiyama, H
Abstract: Background: Hypertension and diabetes mellitus frequently coexist; however, it has not yet been clarified if the bidirectional longitudinal relationships between arterial stiffness and hypertension are independent of those between arterial stiffness and diabetes mellitus. Methods: In this 16-year prospective observational study, 3960 middle-aged employees of a Japanese company without hypertension/diabetes mellitus at the study baseline underwent annual repeated measurements of the blood pressure, serum glycosylated hemoglobin A1c levels (HbA1c), and brachial-ankle pulse wave velocity (baPWV). Results: By the end of the study period, 664, 779, 154, and 406 subjects developed hypertension, prehypertension, diabetes mellitus, and prediabetes, respectively. Increased baPWV at the baseline was associated with a significant odds ratio (per 1 standard deviation increase) for new onset of prehypertension/hypertension with (2.45/3.28, P<0.01) or without (2.49/2.76, P<0.01) coexisting prediabetes/diabetes mellitus, but not for new onset of prediabetes/diabetes mellitus without coexisting hypertension. Analyses using the latent growth curve model confirmed the bidirectional relationships between baPWV and hypertension, but no such relationship was observed between baPWV and abnormal glucose metabolism. Moreover, after the adjustments, higher mean blood pressure at baseline accelerated the increases in the baPWV over follow-up (unstandardized coefficient [B] = 0.39, standard error [SE] = 0.05x10 –1, P<0.01). Similarly, higher baPWV at baseline accelerated the increases in mean blood pressure over follow-up (B = 0.02x10 –1, SE = 0.01x10 –1, P<0.01) (Figure 1). On the other hands, higher HbA1c levels at baseline accelerated the increases in the baPWV over follow-up (B = 0.43, SE = 0.05x10 –1, P<0.01), but higher baPWV at baseline did not accelerate the increases in HbA1c levels over follow-up (B <0.01, SE <0.01, P=0.52) (Figure 2). Conclusions: In middle-aged employees of a Japanese company, in contrast to the bidirectional relationships that exist between arterial stiffness and hypertension, increased arterial stiffness preceding the development of diabetes mellitus may represent that associated with the development of hypertension, as it is observed only in cases of diabetes mellitus coexisting with hypertension. Therefore, arterial stiffness may be associated to a greater degree with the development of hypertension than with the development of diabetes mellitus. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Omron Health Care Company (Kyoto, Japan), Teijin Pharma Company (Tokyo, Japan)